In vitro regeneration of double haploid line of African marigold (Tagetes erecta) derived from ovule culture using non-axillary explants - MEHRAJ, UZMA; PANWAR, SAPNA; SINGH, KANWAR PAL; Namita, NAMITA; PANDEY, RENU; SOLANKE, AMOLKUMAR U; MALLICK, NIHARIKA; KUMAR, SURENDRA (The Indian Journal of Agricultural Sciences, 2019)
An efficient protocol has been developed for in vitro regeneration of double haploid line of African marigold variety Local Orange derived through ovule culture. Maximum survival (85%) of leaf explant was found in the treatment comprising of Bavistin (0.2%), Ridomil (0.2%) and 8-HQC (200 ppm). The surface sterilization treatment of explants with mercuric chloride (0.1%) for 3 minutes resulted in maximum survival (88.33%) and minimum contamination (18.33%). Three different portions of leaf explant (Tip, middle and basal) were used for regeneration. The treatment comprising MS medium supplemented with BAP (0.5 mg/l) and NAA (0.25 mg/l) resulted in maximum percent regeneration (86.25), lowest number of days taken for callus initiation (3.05), minimum number of days for shoot regeneration (13.25), maximum number of micro shoots per explant (3.50), minimum number of days to reach the stage of sub culturing (5.75) with basal portion of leaf explant. Among the different explants, basal portion of the leaf was found as the best explant for maximum regeneration. The basal portion of the leaf explant was further treated with best regeneration treatment, i. e. BAP (0.5 mg/l) and NAA (0.25 mg/l) along with different concentrations of putrescine and it was observed that maximum percent regeneration (89.83%), minimum number of days for shoot regeneration (13.50), maximum number of micro shoots per explant (6.25) and minimum number of days to reach the stage of subculturing (5.75) were found in the treatment combination of BAP (0.5 mg/l), NAA (0.25 mg/l) and Putrescine (50 mg/l).